Personality traits, entrepreneurial self-efficacy, and entrepreneurial intention among vocational students - Juhari, Halimatun Saadiah; Ismail, Normala; Roslan, Samsilah; Zaremohzzabieh, Zeinab (Institute of Advanced Engineering and Science, 2023)
Entrepreneurship in technical and vocational education is a current and relevant topic. While the role of entrepreneurial self-efficacy (ESE) and personality traits as determinants of entrepreneurial intention (EI) has been extensively studied, the role of ESE and personality traits as determinants of vocational students’ EI is still poorly understood. Thus, this study employed ESE and big five personality traits to explore the determinants of EI among vocational college students. This study’s survey had a sample size of 162 technical vocational education and training (TVET) college students, enrolled in technology in automotive, technology in welding, and technology in refrigeration and air conditioning programs. Data were analyzed using Pearson Correlation and Multiple Linear Regression. The results indicate that apart from neuroticism, openness to experience, conscientiousness, agreeableness, and extraversion were positively associated with EI. The results also confirm that ESE is a predictor of EI. Going forward, the article intends to contribute to a better understanding of ESE and personality traits that influence vocational students’ EI, as well as provide some important insights into the unique aspects of TVETs that empower youth to actively participate in micro-entrepreneurial initiatives. This study encourages academics and policymakers to reconsider the approach used in entrepreneurship education in the vocational setup.